2021
DOI: 10.13057/biodiv/d220230
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a farmer-preferred maize landrace population from a multiple-stress-prone subtropical lowland environment

Abstract: Abstract. Makore F, Gasura E, Souta C, Mazamura U, Derera J, Zikhali M, Kamutando CN, Magorokosho C, Dari S. 2021. Molecular characterization of a farmer-preferred maize landrace population from a multiple-stress-prone subtropical lowland environment. Biodiversitas 22: 769-777.  The study was conducted to assess genetic diversity of 372 maize lines using 116 single nucleotide polymorphism (SNP) markers. Three hundred and forty-seven lines were S1 lines (coded J lines) from a local maize landrace population and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Duplications show high level of genetic similarities (Makore et al 2021) which was revealed in this study which is consistent with the findings from the phylogenetic tree that shows low genetic distances between some lines. Seemingly, the observations of duplications and minimal genetic distances indicates that there are introductions that were given different names by different breeders.…”
Section: Population Structure and Genetic Diversitysupporting
confidence: 92%
“…Duplications show high level of genetic similarities (Makore et al 2021) which was revealed in this study which is consistent with the findings from the phylogenetic tree that shows low genetic distances between some lines. Seemingly, the observations of duplications and minimal genetic distances indicates that there are introductions that were given different names by different breeders.…”
Section: Population Structure and Genetic Diversitysupporting
confidence: 92%